Improving Elementary School Students’ Learning Outcomes in Islamic Religious Education on the Topic of Asmaulhusna Using the Make a Match Method - Hafiza, Rikasti; Amaliyah, Aam; Sukarno, Sukarno (Academia Edu Cendekia Indonesia (AEDUCIA), 2026)
Background: Islamic Religious Education in elementary school plays a vital role in instilling faith, moral values, and religious principles in students from an early age. However, in practice, Islamic Religious Education is often delivered through conventional lecture methods and textbooks, resulting in low student interest and limited understanding of the material, particularly Asmaulhusna. Objective: This study aimed to determine the improvement in students’ Aqidah learning outcomes through the implementation of the Make a Match method at SDN 11 Bengkulu Selatan. Method: This research employed a Classroom Action Research (CAR) approach conducted in three cycles during the first semester of the 2024–2025 academic year, specifically in September. The research subjects consisted of 20 fourth-grade students at SDN 11 Bengkulu Selatan. Data were collected through written tests to measure learning outcomes and classroom observations conducted by the teacher during the learning process. Findings: The results showed that implementing the Make a Match method significantly improved students’ learning outcomes. The percentage of mastery learning increased from 55% in Cycle I to 75% in Cycle II and to 90% in Cycle III. These findings indicate that the Make a Match method is effective in helping students understand Aqidah material, particularly Asmaulhusna, in a more interactive and enjoyable way. Conclusion: The Make a Match method significantly enhances students’ Aqidah learning outcomes and can serve as an effective alternative instructional strategy. Contribution: This study contributes by providing an innovative instructional model that teachers can use to enhance student engagement, motivation, and understanding of Islamic Religious Education in elementary school. It also offers a foundation for further research in similar religious education contexts.